Pigment epithelium-derived factor (PEDF) normalizes matrix defects in iPSCs derived from Osteogenesis imperfecta Type VI. Issue 1 (1st January 2016) - Belinsky, Glenn S.; Ward, Leanne; Chung, Chuhan
ABSTRACT: Osteogenesis imperfecta (OI) Type VI is characterized by a defect in bone mineralization, which results in multiple fractures early in life. Null mutations in the PEDF gene, Serpinf1, are the cause of OI VI. Whether PEDF restoration in a murine model of OI Type VI could improve bone mass and function was previously unknown. In Belinsky et al, we provided evidence that PEDF delivery enhanced bone mass and improved parameters of bone function in vivo . Further, we demonstrated that PEDF temporally inhibits Wnt signaling to enhance osteoblast differentiation. Here, we demonstrate that generation of induced pluripotent stem cells (iPSCs) from a PEDF null patient provides additional evidence for PEDF's role in regulating extracellular matrix proteins secreted from osteoblasts. PEDF null iPSCs have marked abnormalities in secreted matrix proteins, capturing a key feature of human OI Type VI, which were normalized by exogenous PEDF. Lastly, we place our recent findings within the broader context of PEDF biology and the developmental signaling pathways that are implicated in its actions.